EFEKTIVITAS PELAYANAN KELUHAN PELANGGAN PADA BLUD RSUD dr. R. GOETENG TAROENADIBRATA PURBALINGGA - Suwanto, Suwanto; Rosyadi, Slamet; Kurniasi, Denok (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2020)
Demands for health service providers in facing the free market era, including the improvement of hospital health services towards world-class hospital services. The problem of the effectiveness of customer complaints services can be seen from the number of people who use the media that has been provided to convey criticism and complaints about the services provided by hospital management. The importance of research aims to determine and analyze the achievement of the implementation of customer complaint handling services. This study uses qualitative research methods with a descriptive approach. The study was conducted at Hospital of dr. R. Goeteng Taroenadibrata Purbalingga. The informants consisted of management elements and customer determined using a purposive sampling technique. The focus of the study in this research includes the achievement of customer complaint services which include the achievement of objectives, integration of complaint handling and the adaptation of the complaint service unit to complaints submitted. Data analysis was performed using the descriptive interactive model analysis method. The results showed that the achievement of customer complaint services at the Hospital of dr. R. Goeteng Taroenadibrata Purbalingga has not been effective. Empirically the function and role of the complaint service that is the main task has been carried out, but has not been fully implemented effectively. Follow-up on complaints submitted by the community has not completely met the expectations of the community, especially concerning the timeliness and accuracy of the actions taken to resolve the problem, as well as completeness